Inclusive mentorship of pediatric trainees: pediatric oncology as a microcosm - Jackson, Sadhana; Tsai, Jessica W.; MacQuarrie, Kyle L. (Frontiers in Oncology, 2025)
Mentorship is a critical part of career development for medical professionals. Mentees find value in mentors who share parts of their identity, and this role-modeling improves career development. In pediatric hematology-oncology specifically – reflective of academic medicine more broadly - the current pool of mentors is less diverse than the pool of mentees. Mentoring consciously in an inclusive manner is a way to support all mentees, not just those who share identity with the mentor. Utilizing skills such as microintervention and bystander intervention, all while focusing on allyship are tools that mentors can develop and use to improve their mentoring practices.